THE PHENOMENON OF PROFESSIONAL DEFORMATION AS AN ASPECT OF TEACHERS’ EMOTIONAL BURNOUT - Kassenova A.B., Kassenova A.B. (Рroblems of engineering and professional education, 2023)
The article is devoted to the emotional burnout of the personality, which manifests itself increasing emotional exhaustion, leading both to personal discomfort among specialists, and to a serious decrease in work efficiency.